New Zealand television and the struggle for `public service - Dunleavy, Trisha (Media, culture & society, 2008)
Public service broadcasting (PSB) objectives have played an important role in New Zealand television since the medium's inception in 1960. In particular, they have helped to ensure that, in a context in which primetime broadcasts can be so easily dominated by cheaply acquired foreign programmes, television can offer a diversity of locally produced material, including some with the potential to foster a sense of 'New Zealand' identity. Nonetheless, the pursuit of public service in New Zealand television has been a struggle in three main respects: (1) New Zealand's limited market size has made it difficult to consistently fund its objectives in programming; (2) there have been fluctuations in its policy and legislative expectations; and (3) most overtly in the 1990s, public service TV has been subject to political neglect of its funding needs. This article examines the provisions for and pursuit of 'public service' in relation to three main phases of New Zealand television: the public monopoly before 1989; the deregulated 1990s; and the early post-millennium era. [PUBLICATION ABSTRACT]